Lipase-produced hydroxytyrosyl eicosapentaenoate is an excellent antioxidant for the stabilization of omega-3 bulk oils, emulsions and microcapsules - TO Akanbi; Colin Barrow (2018)
In this study, several lipophilic hydroxytyrosyl esters were prepared enzymatically using immobilized lipase from Candida antarctica B. Oxidation tests showed that these conjugates are excellent antioxidants in lipid-based matrices, with hydroxytyrosyl eicosapentaenoate showing the highest antioxidant activity. Hydroxytyrosyl eicosapentaenoate effectively stabilized bulk fish oil, fish-oil-in-water emulsions and microencapsulated fish oil. The stabilizing effect of this antioxidant may either be because it orients itself with the omega-3 fatty acids in the oil, thereby protecting them against oxidation, or because this unstable fatty acid can preferentially oxidise, thus providing an additional mechanism of antioxidant protection. Hydroxytyrosyl eicosapentaenoate itself was stable for one year when stored at -20 °C.